Anaerobic fungi: Neocallimastigomycota - G.W. Griffith; S. Baker; K. Fliegerova; A. Liggenstoffer; M. van der Giezen; K. Voigt; G. Beakes (IMA Fungus)
This contribution is based on the six oral presentations given at the Special Interest Group session on anaerobic fungi held during IMC9. These fungi, recently elevated to the status of a separate phylum (Neocallimastigomycota), distinct from the chytrid fungi, possess several unique traits that make their study both fascinating yet challenging to mycologists. There are several genome sequencing programs underway in the US but these are hampered by the highly AT-rich genomes. Next-generation sequencing has also allowed more detailed investigation of the ecology and diversity of these fungi, and it is apparent that several new taxa beyond the six genera already named exist within the digestive tracts of mammalian herbivores, with others potentially inhabiting other anaerobic niches. By increased collaboration between the various labs studying these fungi, it is hoped to develop a stable taxonomic backbone for these fungi and to facilitate exchange of both cultures and genetic data.